Spain: Intergenerational Solidarity – Exploring the Impact of Demographic Change on Family Dynamics and Social Policy - Gas-Aixendri, Montserrat (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
This chapter delves into the multifaceted theme of intergenerational solidarity, a subject of growing importance catalysed by the European Union’s designation of 2012 as the European Year of Active Ageing and Solidarity between Generations. Against the backdrop of Spain’s demographic transformation, characterised by increased longevity and declining fertility rates, the imperative to establish sustainable and equitable intergenerational relationships transcends national boundaries. This chapter shows that stronger intergenerational solidarity within the family matches with other cumulative effects, in particular in relation to family social capital, which proves to be generated by intergenerational family solidarity and, in turn, helps multiply it. The circumstances surrounding the study reported in this chapter facilitated collaboration among institutions engaged in research on intergenerational solidarity in Southern Europe. Motivated by the European Year, the Università Cattolica del Sacro Cuore in Italy conducted a study from 2012 to 2014 titled ‘“I Don’t Want to Be Inactive” – A Longer Life: A Generational Challenge and an Opportunity for Society’. Collaboration networks among researchers enabled the Institute for Advanced Family Studies at the Universitat Internacional de Catalunya to establish a parallel investigation in Spain within the framework of institutional cooperation between these two academic entities, adapting the study’s content to Spain’s unique circumstances and research objectives. In this chapter, we embark on a brief review of the two primary studies conducted in Spain on the subject of intergenerational family solidarity. Keywords: Intergenerational solidarity; family relationships; active ageing; demographic change; social policy